(untitled) (Tanzania Journal for Population studies and Development, 2021)
This article compares two types of collaborative governance initiatives in fisheries management in Tanzania for managing coastal resources, namely, the Beach Management Units and Mnazi-Bay Ruvuma Estuarine Marine Park. The initiatives claim to involve communities and ensure socioeconomic livelihood. The comparison aimed at proposing the best approach in the management of coastal resources to policy makers. Several methods were used in the study that informed this article. These included household surveys, interviews and field observation. Generally, the findings show that the two collaborative governance initiatives have introduced what we call ‘projectized’ forms of livelihoods that are not sustainable due to their poor consideration of community needs and practices. ‘Projectized’ here means livelihood activities that operate in terms of projects and, therefore, have a timeframe for their operation. The article concludes that the establishment of any income generating activity in a community should take into account the community’s needs and its cultural forms of livelihood to ensure the sustainability of such activities. Hence, we recommend that, when introducing any kind of collaborative governance initiative, communities should be empowered to gain capacity to run and operate the established livelihood activities for a long time.